Compositional shifts in soil bacterial communities from polar and tropical regions in response to simulated warming - Chua, Chuen Yang (2020)
The effects of global warming are increasing evidently in various biomes, and it is expected that soil bacterial diversity will be affected as they adapt towards higher environmental temperatures. However, the extent of changes may differ between distinct environments, such as between the tropical and polar region. This study aims to investigate the effects of simulated warming on bacterial diversity in soils from Kota Kinabalu (KK), Sabah and South Shetland Islands, Antarctica. Simulated warming was carried out using open-top chambers (OTC) at three plots in Kota Kinabalu for one year, while soils from two South Shetland Islands, specifically King George Island (KGI) and Deception Island (DCI), were placed in a growth chamber that simulates tropical-like conditions based on climate data obtained from Sabah Meteorological Department. Changes in bacterial diversity of tropical and polar soils in this study were monitored using V3-V4 16S rDNA amplicon sequencing. Optimization of DNA extraction method was first carried out using three different methods on ten soil samples collected around KK to avoid underestimation of soil bacterial diversity. The highest genomic DNA concentration was obtained using Method 1 (10.70 to 92.98 μg/g of soil), while DNA purity was highest for Method 3 with average A280/A260 and A260/A230 ratios of 1.91 and 1.76 respectively. Higher DNA purity achieved using Method 3 can be attributed to the use of silica spin columns to remove soil contaminants. Results from PCR-DGGE analysis showed that bacterial diversity in the soils from KK were underestimated using Method 1 and 2, mainly due to PCR inhibition by co-extracted contaminants such as humic acid. As for Method 3, total number of DGGE bands and Shannon-Weaver indices were the highest, which indicated that Method 3 gave the most accurate representation of soil bacterial diversity in KK soils. Method 3 was therefore the most suitable DNA extraction method for KK soils in this study. Simulated warming using OTCs on KK soils led to an average increase of 0.81 to 1.15 °C in treatment plots after 12 months. V3-V4 16S rDNA amplicon analysis showed that initial bacterial diversity in KK soils were predominated with Actinobacteria, Acidobacteria and Proteobacteria at phylum level; Gaiella, Candidatus Koribacter and Candidatus Solibacter spp. at genus level. Significant changes in relative abundance of bacterial phyla Bacteroidetes and Chloroflexi were detected after 12 months of simulated warming. Increases in relative abundance of Actinobacteria and Planctomycetes were also observed in treatment plots. Substantial changes were observed at genus level, where relative abundance of Gaiella, Bradyrhizobium and Chthoniobacter decreased substantially after 12 months of incubation. Substantial increase in relative abundance of Bacillus was also detected, where RT-PCR analysis confirmed the presence of pathogenic bacteria from this bacterial group in the KK soils. Initial diversity of soil bacteria phyla was determined for KGI and DCI soils, which mainly include Actinobacteria, Proteobacteria and Verrucomicrobia. Comparisons at genus level showed different compositions of bacteria between KGI and DCI soils, where Gaiella spp. was predominant in KGI soils while bacterial genera in DCI soils were more evenly distributed. Initial DGGE analysis provided evidence that 12 months of simulated tropical-like conditions led to significant changes in overall bacterial diversity of KGI soils, but not for DCI soils. V3-V4 16S rDNA amplicon analysis showed that most bacterial phyla in both soils did not thrive after 12 months of simulated tropical-like conditions. There were however increases in relative abundance of Proteobacteria by more than 150 % in KGI soils, while a twofold increase in relative abundance was observed for Acidobacteria and Chloroflexi in DCI soils. Substantial changes in bacterial composition were also observed at genus level, where Methylobacterium spp. was most predominant in both soils after 12 months of incubation. The genus Methylobacterium may consist of opportunistic human pathogens, which warrants further monitoring. Increases in relative abundance of potentially pathogenic bacteria such as Mycobacterium, Massilia and Williamsia spp. were detected, and further validation will be required to determine pathogenicity of these bacterial genera, if any. Overall, the results of this study provided baseline diversity of soil bacteria at sites in Kota Kinabalu and South Shetland Islands. This study gave an indication of how soil bacteria from KK would respond towards soil warming in the coming decades, assisting in potential microbial conservation efforts and related future studies. The response of soil bacteria from KGI and DCI towards simulated tropical-like conditions also highlighted the importance of preventing accidental transfer of soils out of Antarctica.